Repeated-sprint training with blood-flow restriction improves repeated-sprint ability similarly to unrestricted training at reduced external loads - Mckee, J. R.; Girard, O; Peiffer, J. J.; Hiscock, D. J.; De Marco, K.; Scott, B. R. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study examined performance and physiological adaptations following 3 weeks of repeated-sprint training (RST) with blood-flow restriction (BFR) or without (non-BFR).